2023
DOI: 10.1186/s40001-023-01562-0
|View full text |Cite
|
Sign up to set email alerts
|

The clinical association between coagulation indexes, platelet-related parameters, and bone metastasis of newly diagnosed prostate cancer

Zhiwei Yu,
Mingxue Yuan,
Guojun Chen

Abstract: Background At present, much evidence shows that many cancers have a high risk of thrombosis. Several studies have shown the prognostic value of platelet-related parameters and coagulation indexes in prostate cancer (PCa). However, the association between platelet-related parameters, coagulation indexes and bone metastasis of Pca is unclear. Methods A total of 234 pathologically diagnosed patients with Pca were consecutively collected and stratified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Similarly, Albayrak et al found RDW to be predictive of an increased risk of PCa, further underscoring its role in disease progression (Albayrak et al 2014). Furthermore, Yu Z et al identi ed a link between elevated platelet counts and poorer prognoses in PCa, adding another layer to the complex relationship between hematological markers and cancer outcomes (Yu et al 2023). Complementing these ndings, Song W et al reported that integrating platelet distribution width with total or free prostate-speci c antigen levels could re ne the diagnostic precision for PCa, enhancing the clinical value of PSA testing (Song et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Albayrak et al found RDW to be predictive of an increased risk of PCa, further underscoring its role in disease progression (Albayrak et al 2014). Furthermore, Yu Z et al identi ed a link between elevated platelet counts and poorer prognoses in PCa, adding another layer to the complex relationship between hematological markers and cancer outcomes (Yu et al 2023). Complementing these ndings, Song W et al reported that integrating platelet distribution width with total or free prostate-speci c antigen levels could re ne the diagnostic precision for PCa, enhancing the clinical value of PSA testing (Song et al 2022).…”
Section: Discussionmentioning
confidence: 99%